'Pas d'hospitalité': Derrida and the study of hospitality in higher education. Issue 2 (1st June 2017) - Hemmington, Nigel; Gibbons, Andrew
This article explores Jacques Derrida's deconstruction of hospitality within the context of the study of hospitality in higher education. The contribution of Derrida's work is discussed, and then Derrida's thoughts on the possibility of hospitality are explored in relation to hospitality education. The implications of absolute (unconditional) hospitality, reciprocity, generosity, transactions and the Internet are then explored within the context of Derrida's thinking, particularly his possible–impossible aporia. This conceptual approach is presented in an anticipation that these ideas will create astonishment that will stimulate new and different approaches to thinking about hospitality, and will in turn have implications for hospitality education and the hospitality industry.